2021
DOI: 10.1177/01455613211044778
|View full text |Cite
|
Sign up to set email alerts
|

Pilomatrixoma and its Imitators

Abstract: Introduction: Pilomatrixomas are benign neoplasms derived from hair follicle matrix cells. They are among the most common soft tissue head and neck tumors of childhood. Pilomatrixomas are typically isolated, slow-growing, firm, nontender masses that are adherent to the epidermis but mobile in the subcutaneous plane. This clinical presentation is so characteristic that many experienced surgeons will excise suspected pilomatrixomas without prior imaging. We reviewed the results of this approach to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…By contrast, pilomatricoma of the auricle was rarely reported. One retrospective study has shown that pilomatricoma of the auricle may lead to misdiagnoses because of its close clinical resemblance to other skin conditions such as a dermoid cyst compared with cases involving other body parts [ 6 ]. In addition, given the rarity of its occurrence in the auricle, clinicians may initially consider other differential diagnoses that are commonly found in this area, such as squamous cell carcinoma, or those that almost exclusively occur in the auricle, such as tumors of the ceruminous gland [ 11 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, pilomatricoma of the auricle was rarely reported. One retrospective study has shown that pilomatricoma of the auricle may lead to misdiagnoses because of its close clinical resemblance to other skin conditions such as a dermoid cyst compared with cases involving other body parts [ 6 ]. In addition, given the rarity of its occurrence in the auricle, clinicians may initially consider other differential diagnoses that are commonly found in this area, such as squamous cell carcinoma, or those that almost exclusively occur in the auricle, such as tumors of the ceruminous gland [ 11 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, diverse clinical variants have been described, including perforating, anetodermic, proliferating, and pigmented types [ 4 , 5 ]. Consequently, pilomatricoma may mimic various skin conditions, such as epidermoid and dermoid cysts, trichilemmal cysts, and steatocystoma [ 6 ]. Diagnosis of pilomatricoma is dependent on histologic findings, which are characterized by islands of tumors in the dermal or subcutaneous layer, encompassing two types of cells, namely, basaloid matrical cells in the periphery and classic anucleated “ghost” cells toward the center, with variable areas of calcification [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically they often present as a firm, freely movable, slow‐growing mass in the children. They are commonly seen in the head and neck and their size of generally vary between 0.5 and 3 cm 35,36 …”
Section: Solid Neck Massesmentioning
confidence: 99%
“…They are commonly seen in the head and neck and their size of generally vary between 0.5 and 3 cm. 35,36 On US, they typically appear as a well-defined subcutaneous mass with strong posterior acoustic shadowing. Color Doppler may show little peripheral vascularity (Figure 11).…”
Section: Pilomatricomamentioning
confidence: 99%
“…The incidence is not precise, but it is reported between one and three in 1,000 dermatohistopathologic specimens examined [ 1 ]. It usually presents as a solitary firm painless subcutaneous slow-growing mass, attached to the skin with no invasion of the underlying tissue [ 1 , 2 , 5 , 8 ]. Its dimensions often range from 0.5 to 3 cm, but lesions greater than 5 cm in diameter can be seen and are described as giant pilomatrixoma [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%